Intensifikasi Program Pemampatan Kompetensi Dasar untuk Meningkatkan Efektivitas Mengajar Secara Daring - Etiek Dyah Prasetyanti Haryono (Departement of Mathematics Education, 2021)
This study summarizes as well as briefly and concisely informs the various activities that have been carried out by the Education Office related to the implementation of the compression of Basic Competencies. For teachers, there are rarely seminars or workshops that explore the process behind a policy and photograph it up close, revealing the concerns and hopes of the actors by maintaining credibility and transparency. It can be said, this policy is still gray in the midst of reality of the implementation of Community Activity Restrictions (PPKM) which has not ended since the beginning of the new school year and the discourse on the implementation of Limited Face-to-face Learning (PTMT). This action research was carried out at SD Negeri Wiyung I/453, Wiyung sub-district, Surabaya City by involving 28 classroom teachers as research subjects from August to September 2021. This research was action research because the writer who carried out the action was the principal of SD Negeri Wiyung I/453 who fully responsible for the development of human resources in the school environment. Based on data analysis, from this study it can be concluded that the intensification of the Basic Competence Compression Program through Workshops and Online Teaching Socialization is very effective. The attitudes and abilities of teachers at SD Negeri Wiyung I/453 Surabaya for the 2021/2022 academic year improved after the Workshop. In addition, it can also improve the ability of teachers professionally in Online Teaching. This can be seen in the second cycle of activities after the intensification of the Basic Competence Compression Program through Workshops and Socialization the average score obtained was 70.3. Learning is said to be effective if at least 65% of the criteria can be met. Thus, it can be stated that in the first and second cycles 100% of teachers have effectively taught online in the 2021/2022 school year.